Analysis of affordability of meat, chicken, fish or vegetarian equivalent every second day in households in Latvia - Sloka, Biruta; Jekabsone, Inga (My University, 2019)
In recent years, there are growing research and policy discussions on assessment and analysis of poverty and measurement of material conditions. Researchers and policy makers develop different set of indicators that describes material deprivation. Material deprivation that is usually defined as the extent of functioning failures in the dimension of material well-being is based on set of different items that refer to affordability of basic needs. Affordability of meat, chicken, fish or vegetarian equivalent every second day is one of main indicators that characterizes meeting the basic needs of the households. In case of Latvia, macroeconomic indicators show that through recent years country is going on economic recovery path, however there are discussions on growing income inequality and poverty in regions. Taking into account before mentioned, the aim of the paper is to analyse the material deprivation and food poverty by assessing the affordability of meat, chicken, fish or vegetarian equivalent every second day in households in Latvia. The tasks are formulated as follows: 1) To review theoretical background on measuring the material deprivation and food poverty in households; 2) To assess empirical research on measuring the material deprivation and food poverty in households; 3) To analyse statistical data on households’ affordability in Latvia. In order to achieve the aim, following research methods have been used: scientific literature studies, statistical data analysis. Main results and conclusions of the paper: there is wide range of indicators and indexes that measure food poverty and material deprivation. Based on these measures policy makers develop framework for social inclusion and inclusive society. In case of Latvia, analysis of affordability of on measuring the material deprivation and food poverty in households showed that there is positive trend over the years in regards to the share of people that cannot afford to meet their basic needs. However, the situation is rather critical in some regions of Latvia.
Keywords: inclusive society; food poverty; material deprivation; Research Subject Categories::SOCIAL SCIENCES::Business and economics